(untitled) - Sabol, Stuart (Chichester, West Sussex, U.K., 2016)
Case Studies in Mechanical Engineering provides real life examples of the application of engineering fundamentals. They relate to real equipment, real people and real decisions. They influence careers, projects, companies, and governments. The cases serve as supplements to fundamental courses in thermodynamics, fluid mechanics, heat transfer, instrumentation, economics, and statistics. The author explains equipment and concepts to solve the problems and suggests relevant assignments to augment the cases.
Keywords: Mechanical engineering,Kỹ thuật cơ khí; Case studies,Nghiên cứu trường hợp